Increasing the Profitability of Pottery MSMEs through Financial Efficiency and Production Optimization in Tabanan Regency - Bevi Libraeni; Mila Rosa Desmayani; Nonik Erawati; Rudiharta Pratama Giri (Jurnal Ekonomi Manajemen Bisnis dan Akuntansi, 2026)
This study aims to analyze strategies for increasing the profitability of pottery Micro, Small, and Medium Enterprises (MSMEs) through financial efficiency and production process optimization in Tabanan Regency, Bali. The research employed a mixed-method approach combining qualitative and quantitative analysis through literature review, secondary data analysis, and case studies involving selected pottery MSMEs. Data were obtained from financial records, production reports, and interviews with business owners, and were analyzed using comparative descriptive analysis to assess conditions before and after the implementation of efficiency strategies. The findings indicate that the implementation of structured financial management, including cash flow planning and raw material inventory control, reduced operational costs by approximately 20%. Meanwhile, production optimization through process standardization and the adoption of simple technologies, such as controlled firing systems, increased daily production capacity by up to 30% and reduced defect rates. Furthermore, product diversification and digital marketing strategies expanded market reach and improved revenue stability. This study highlights the importance of integrating financial efficiency, production optimization, innovation, and risk management to support sustainable growth and enhance the competitiveness of pottery MSMEs.